The Effect of Podcast-Based Learning Media on the Speaking Skills in Islamic Cultural History (SKI) of MTs Raudhatul Jannah NW Bengkang Students - Abdurrahman, Abdurrahman; Mazani, Tamimi; Basri, Hasan; Sholihin, Muhammad; Supardi, Supardi (AS-SABIQUN, 2025)
This study examined the effect of podcast-based learning media on students’ speaking skills in Islamic Cultural History (SKI) at MTs Raudhatul Jannah NW Bengkang, Indonesia. It aimed to evaluate the impact on speaking performance, analyze students' perceptions of podcasts as a learning tool, and assess their influence on engagement and motivation. A pre-experimental one-group pre-test and post-test design was used, involving 28 Class VII students as the sample. Data were collected through pre-tests, post-tests, and a Likert-scale questionnaire. Speaking skills were assessed based on pronunciation, fluency, vocabulary usage, and content relevance, while questionnaire responses measured engagement, ease of use, and perceived effectiveness. The findings revealed a significant improvement in students’ speaking skills, with the mean score increasing from 60.5 (SD = 8.4) in the pre-test to 79.3 (SD = 7.2) in the post-test (p = 0.002). Questionnaire feedback indicated high levels of engagement (85%), ease of use (78%), and perceived effectiveness (82%). The results demonstrated that podcast-based learning media served as an innovative and effective tool to enhance speaking skills and engagement in Islamic education. This study concluded that podcasts improved measurable outcomes and fostered positive perceptions and motivation among students. The findings suggested that podcast-based learning media could be broadly applied in similar educational contexts to support student-centered and interactive learning approaches.